SECTION I Veterinary Anesthesia and Analgesia. Research papers and case reports.: Anestesia y Analgesia Veterinaria. Trabajos de Investigación y reportes de casos (Veterinary Science, 2022)
Analgesia y Anestesia Veterinaria : COMISION ACADEMICA Y CIENTIFICAMV. de Genaro, Mariana ( Práctica privada)Dr. Lorenzutti, Matías (Universidad Católica de Córdoba)Esp. Miguel, María Carolina (Universidad Nacional de La Pampa)Dr. Nejamkin, Pablo ( Universidad Nacional del Centro de la Pcia. de Buenos Aires)Dr. Otero, Pablo (Universidad de Buenos Aires)MV Robledo, Oscar ( Universidad Nacional de La Plata)Dr. Tarragona, Lisa (Universidad de Buenos Aires)
Keywords: Cardiac output; Hemodynamics; Levomepromazine; Masks; Atelectasis; Intra-Surgical Nociception; Post-Surgical Pain; Fluid challenge; Cardiorespiratory interaction; Fluid resuscitation; Dynamic variables; Cardiac Output; Canines; Anesthesia; Mechanic ventilation; Mandibulectomy; Snake; Resection; laryngeal paralysis; TIVA; Propofol; Blocking; Hen; Brachial plexus; Chylothorax; Amphibians; Axolotl; Lung volumes; Chest circumference; Ventilation programming; Positive pressure at the end of expiration; Ultrasonography; Neuro-monitoring; Aortic Doppler; Renal Doppler; Femoral Doppler; Sex; Height; Sedation; Swine; α-2 Adrenergic agonists; Domestic chicken; Corpse; Dorsal approach; Ecoguided